2018
DOI: 10.1021/acs.jmedchem.8b00817
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy-Driven Stabilization of Transthyretin by AG10 Mimics a Naturally Occurring Genetic Variant That Protects from Transthyretin Amyloidosis

Abstract: Transthyretin (TTR) amyloid cardiomyopathy (ATTR-CM) is a fatal disease with no available disease-modifying therapies. While pathogenic TTR mutations (TTRm) destabilize TTR tetramers, the T119M variant stabilizes TTRm and prevents disease. A comparison of potency for leading TTR stabilizers in clinic and structural features important for effective TTR stabilization is lacking. Here, we found that molecular interactions reflected in better binding enthalpy may be critical for development of TTR stabilizers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(110 citation statements)
references
References 41 publications
4
106
0
Order By: Relevance
“…The Kd for the binding of a stabilizer to TTR is represented by the change in the Gibbs free energy of binding (ΔG), where ΔG = ΔH − TΔS. This technique has been used previously to compare small-molecule TTR stabilizers, like the small-molecule AG10 with other TTR tetramer stabilizer drugs [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kd for the binding of a stabilizer to TTR is represented by the change in the Gibbs free energy of binding (ΔG), where ΔG = ΔH − TΔS. This technique has been used previously to compare small-molecule TTR stabilizers, like the small-molecule AG10 with other TTR tetramer stabilizer drugs [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Kd values reported in Table 1 were based on data fitted to an independent single-site binding model implemented in Origin 7.0 (OriginLab). Previous ITC studies for the binary complexes of tolcapone and tafamidis with TTR have used either a single model [ 42 ] or a two-site model to approximate binding to TTR [ 24 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…14,26 When AG10 was co-crystallized with tetrameric TTR, this structure revealed that the two nitrogen atoms of AG10's pyrazole ring are similarly capable of forming hydrogen bonds with adjacent serine 117 residues. 14,28 These data suggest a structural basis to expect superior stabilizing properties of AG10 in vivo. No other stabilizer that binds to the thyroxine binding site, including TTR's natural ligand thyroxine, is structurally capable of similar molecular binding interactions.…”
Section: Discussionmentioning
confidence: 83%
“…Such hydrogen bonds can potentially explain the observed 40‐fold slower dissociation rate of the T119M tetramer as compared to the wild type tetramer . When AG10 was co‐crystallized with tetrameric TTR, this structure revealed that the two nitrogen atoms of AG10's pyrazole ring are similarly capable of forming hydrogen bonds with adjacent serine 117 residues . These data suggest a structural basis to expect superior stabilizing properties of AG10 in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…Other agents currently undergoing clinical development for the treatment of ATTRv include novel TTR stabilizers that offer greater stability of TTR tetramers (e.g. tolcapone [SOM0226], CSP-1103 [CHF5074], AG10) [34][35][36][37][38][39][40], combination therapy with doxycycline (disrupts TTR amyloid fibril formation) and tauroursodeoxycholic acid (reduces nonfibrillar TTR deposition) [41,42], and anti-TTR monoclonal antibodies that target amyloid monomers and inhibit fibril formation and promote phagocytosis of TTR aggregates [43][44][45]. While these agents show promise, published data from randomized controlled trials are currently lacking.…”
Section: Overview Of the Marketmentioning
confidence: 99%